Prognostic value of modified Glasgow prognostic score in recurrent high-grade glial tumors treated with systemic treatment - ATASOY, BESTE MELEK; YUMUK, PERRAN FULDEN (ELSEVIER, 2020)
Objectives: Malignant high-grade gliomas are the most common and aggressive type of primary brain tumor. We aimed to evaluate the prognostic value of modified Glasgow Prognostic Score (mGPS), which is combination of C-reactive protein (CRP) and albumin, in recurrent high-grade glioma patients treated with systemic treatment. Patients and Methods: Data of 85 patients with recurrent high-grade glioma who received systemic treatment and followed in our clinic between 2012 and 2018 was retrospectively collected and analyzed. Patients were grouped according to mGPS criteria: mGPS-0: CRP 10 mg/L and albumin 3.5 g/dL or CRP 10 mg/L and albumin > 3.5 g/dL; and mGPS-2: CRP > 10 mg/L and albumin < 3.5 mg/L. We investigated the prognostic role of mGPS groups, mutations and survival outcomes. Results: There were 42 (49.4 %), 25 (29.6 %), and 18 (21 %) patients in mGPS-0, mGPS-1, and mGPS-2 groups, respectively. Median follow-up duration was 10 months (1-70 months). Median OS was 8.1 months. According to mGPS-0,-1 and-2; median OS was 13.8 months, 7.3 months and 3.6 months respectively (p = 0.003). mGPS, ATRX and IDH-1 mutation status, and ECOG PS were found to be independent prognostic factors for OS. Conclusion: In our study, mGPS was found to be an independent prognostic factor in patients with recurrent high-grade gliomas. If validated, mGPS can be used as an objective, easily calculated, cheap, and readily available prognostic model in routine practice.
Keywords: glioblastoma; Glasgow prognostic score; high grade gliomas; ATRX status; overall survival; CENTRAL-NERVOUS-SYSTEM; SINGLE-AGENT BEVACIZUMAB; ACUTE-PHASE RESPONSE; SERUM-ALBUMIN LEVELS; INFLAMMATORY RESPONSE; SURVIVAL; CHEMOTHERAPY; TRIAL; IL-6; GPS